Orientation-Workshop on Normative Funding for SUCs/Campuses in Region-IX and Utilization of Income Generating: An Impact Study - Remoto, Jocelyn; Climaco, Christopher (JPAIR Multidisciplinary Research, 2017)
The purpose of this impact study was to determine the relevant learning experiences of the ZCSPC participants in the Orientation-Workshop on Normative Funding for SUCs/Campuses in Region IX and Utilization of Income Generating and how they implemented the learning experiences, relevant to their duties and responsibilities, in the College. The qualitative research design was utilized. The purposive sampling technique was used since the respondents were the identified ZCSPC participants. The data were collected using the one-on-one interview between the respondent and the researcher. The findings revealed the following salient concerns affecting the normative funding: a.) the budget officer did not adopt the Aklan State University model policy on the use of income and opted to follow the ZCSPC’s existing policy on the use of income up to the present; b.) the advice to strictly implement the PhilGEPS was adopted by the College and gradually implemented in its procurement system; c.) the workload misconceptions of the faculty members were given attention through the initial workload policy revision made by the VPTAA (2009). The Administration resorted to the hiring of visiting lecturers and the implementation of the biometric system until the faculty members fully understood the workload policy through the CHED-HEMIS guidelines on August 2013. It is recommended that ZCSPC Administration strictly follow the guidelines set by CMO No. 20, s. 2011; strictly monitor PhilGEPS postings; and fully implement the vertical articulation.